2020
DOI: 10.21203/rs.3.rs-21887/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synergistic effect of ibrutinib and CD19 CAR-T cells on Raji cells in vivo and in vitro

Abstract: KEYWORDSBruton tyrosine kinase inhibitor, Chimeric antigen receptor, Programmed cell death 1 ligand 1, Raji cell line, Tumor microenvironment

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…Furthermore, it was confirmed that the expansion of anti‐CD19‐CAR T cells from 3 CLL patients who had been treated with ibrutinib more than 12 mo improved significantly compared with the anti‐CD19‐CAR T cells before ibrutinib treatment 32 . Our previous study observed that PD‐1 expression of anti‐CD19‐CAR T cells increased when co‐cultured with lymphoma cells in vitro, and ibrutinib could weaken this effect 20 . In this study, the mean expression of PD‐1 on CD3 + T cells in peripheral blood declined after 7‐16 mo of ibrutinib salvage treatment, which is consistent with the previous studies that showed that function of T cells and defective microenvironment in CLL patients were improved through several cycles of ibrutinib therapy 32,35‐37 .…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Furthermore, it was confirmed that the expansion of anti‐CD19‐CAR T cells from 3 CLL patients who had been treated with ibrutinib more than 12 mo improved significantly compared with the anti‐CD19‐CAR T cells before ibrutinib treatment 32 . Our previous study observed that PD‐1 expression of anti‐CD19‐CAR T cells increased when co‐cultured with lymphoma cells in vitro, and ibrutinib could weaken this effect 20 . In this study, the mean expression of PD‐1 on CD3 + T cells in peripheral blood declined after 7‐16 mo of ibrutinib salvage treatment, which is consistent with the previous studies that showed that function of T cells and defective microenvironment in CLL patients were improved through several cycles of ibrutinib therapy 32,35‐37 .…”
Section: Discussionmentioning
confidence: 57%
“…In addition, inhibition of IL‐2‐inducible T‐cell kinase (ITK) activity would lead to the inhibition of Th2 cell differentiation and promotion of a Th1 cell immune response 38 . Our previous study suggested that ibrutinib might have a synergistic effect with anti‐CD19‐CAR T cells by improving the TME 20 . In our study, these 7 patients were all R/R B‐NHL patients with unsatisfactory efficacy of the first‐time anti‐CD19‐CAR T‐cell therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported the e cacy of BTK inhibitors combined with anti-CD19-CAR T cell in vitro, in vivo [30] and in clinical studies [31,32]. In our study, three refractory mantle cell lymphoma (MCL) patients and four refractory FL patients obtained PR or PD in their rst time anti-CD19-CAR T cell therapy.…”
Section: Discussionmentioning
confidence: 78%